1987
DOI: 10.1097/00006254-198701000-00015
|View full text |Cite
|
Sign up to set email alerts
|

An Improved, Efficient Method for Analyzing Human Sperm Chromosomes Using Zona-Free Hamster Ova

Abstract: We have developed an improved method for analyzing human sperm chromosome, using zona-free hamster ova. Our main improvements of methodology are as follows: (1) Fertilization rate of hamster oocytes by human spermatozoa was markedly raised by successive treatments of the spermatozoa with 5-15 piM ionophore A23 187 solutions and a capacitation medium (BWW medium) containing 3.5% HSA. The HSA most effective in inducing capacitation was selected from several kinds of HSA products commercially available. (2) Monos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 10 publications
2
49
2
Order By: Relevance
“…Since the development of an interspecific in vitro fertilization system between human spermatozoa and zona-free golden hamster oocytes [1,2,3,4], a number of cytogenetic studies with human spermatozoa have been carried out during the last two decades [5,6,7,8]. This method has been applied to chromosomal studies of spermatozoa exposed in vitro to various mutagens.…”
Section: Introductionmentioning
confidence: 99%
“…Since the development of an interspecific in vitro fertilization system between human spermatozoa and zona-free golden hamster oocytes [1,2,3,4], a number of cytogenetic studies with human spermatozoa have been carried out during the last two decades [5,6,7,8]. This method has been applied to chromosomal studies of spermatozoa exposed in vitro to various mutagens.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal integrity of rat spermatozoa was analyzed in rat oocytes according to the method reported in mouse oocytes (Kamiguchi and Mikamo, 1986). All the sperm samples after rehydration for ICSI experiments were re-frozen and stored in LN 2 for a few months until the analysis.…”
Section: Chromosomal Analysismentioning
confidence: 99%
“…In 1978, Rudak et al reported a new cytogenetic 382 H. HU el aL technique using human sperm/hamster egg interactions which first permitted a direct analysis of the chromosomal constitution in individual human sperm (Rudak et al, 1978). In this way, human sperm chromosomes have been studied for both numerical and structural aberrations (Brandriff et al, 1984;Martin et al, 1982;Kamiguchi and Mikamo, 1986). However, this method is labor intensive and time consuming, and may reflect natural meiotic selection, since only fertilized eggs can be studied.…”
Section: Introductionmentioning
confidence: 99%